ANALISIS PENGARUH DANA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN NGLEGOK KABUPATEN BLITAR - Verren Elyviana Supriadi; Aris Soelistyo; Yunan Syaifullah (Jurnal Ilmu Ekonomi JIE, 2020)
The purpose of this study is to determine the effect of Village Funds, Capital Expenditures, and Population Amounts for Infrastructure Development in Nglegok District in 2015-2019. This type of research is quantitative descriptive. The type of data used is secondary data obtained from the Office of Community and Village Empowerment (DPMD) in the form of financial statements of the Village Budget (APBDes).Census technique is used to determine the population in this population in this study. The sample of this research is 10 villages in Nglegok District.The data collection technique used is the documentation method. The technical analysis used is panel data regression. The results of this study suggested that the Village Fund variable has a significant positive effect on infrastructure development, the Capital Expenditure variable has a significant positive effect on infrastructure development, and the population has a significant negative effect on infrastructure development in Nglegok District.